Zdrowie publiczne jako problem i inspiracja rozwoju zawodowego na tle innych obszarów pracy zawodowej okresu bezpośrednio powojennego na Ziemiach Zachodnich = Public health as a problem and inspiration of a professional development against a background of other areas of work during the immediately post-war period in the western lands - Owoc, Alfred; Wołk, Zdzisław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the post-war years in the Western Lands there were numerous social problems as a consequence of historical changes. One of the particularly complex problems was the construction of new social structures in completely new collectivities. The article shows the specific activities associated with the formation of health culture and solving health problems in the context of other areas of life.
Keywords: zdrowie publiczne; Ziemie Zachodnie; 1945-1950